Assessing the prevalence of hypocalcemia after total thyroidectomy at a tertiary care hospital - Sarker, Mohammad Shahjahan; Siddique, Mazharul Alam; Islam, M. Zahidul; Hanif, Mohammad; Rahman, M. Mizanur; Hossain, A. B. M. Delowar (International Journal of Research in Medical Sciences, 2024)
Background: Thyroidectomy is a common surgical procedure for various thyroid disorders, but it often leads to complications such as hypocalcemia. Understanding the prevalence and predictors of hypocalcemia post-total thyroidectomy is crucial for improving patient outcomes. Methods: This prospective cross-sectional study was conducted at a tertiary care hospital with 100 patients undergoing thyroid surgery, including total thyroidectomy, completion thyroidectomy, and thyroidectomy with neck dissection. We analyzed the incidence of transient and permanent hypocalcemia, examining correlations with surgery type, demographic variables, and postoperative day of onset. Data were collected through patient records and postoperative follow-ups. Results: The study revealed that 30% of patients experienced hypocalcemia postoperatively. Hypocalcemia was most prevalent among patients undergoing thyroidectomy with neck dissection (58.33%), compared to those undergoing total thyroidectomy (18.18%) and completion thyroidectomy (40.00%). The majority of hypocalcemia cases (66.67%) occurred on the second postoperative day. Most hypocalcemia instances were transient (86.67%), with a smaller fraction being permanent (13.33%). Conclusions: Hypocalcemia remains a significant complication following thyroid surgery, particularly in surgeries involving neck dissection. Early identification and management of at-risk patients could mitigate the severity of this complication. Our findings underscore the importance of vigilant monitoring and tailored postoperative care to minimize the impact of hypocalcemia on patient recovery and quality of life.